Predatory Publishers. Issue 1 (2nd January 2017) - Herron, Jennifer
ABSTRACT: Predatory publishers have been a growing concern since librarian Jeffrey Beall first coined the phrase in 2010. Much like any phishing ploy, predatory publishers know what to exploit, making academic researchers feel pressured to publish and increase their bibliometrics in order to gain funding and earn tenure. Examples of the poor peer review processes of predatory publishers highlights the issues surrounding the research contained in their journals and, while evaluating predatory publishers, traditional journals also have fallen under the microscope for their peer review processes. With predatory publishers gaining more attention and growing at a rapid pace, more information is being published to inform researchers how to detect and avoid these journals. Thanks to Beall's work, librarians are finding their expertise being recognized and may soon find a stronger place in research processes.